Implementasi Program Pembiasaan Membaca 10 Menit dalam Meningkatkan Budaya Literasi Keislaman Siswa di Sekolah Dasar: Implementation of the 10-Minutes Reading Habit Program to Improve Islamic Literacy Culture for Students in Elementary School - Nurhidayah, Dede (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2025)
A culture of literacy is an important foundation in basic education because reading skills are the basis for successful learning at the next level. From an Islamic perspective, the urgency of literacy is further strengthened by the command of Iqra, the first revelation, which emphasizes that reading is the gateway to civilization and a means of acquiring knowledge. This study aims to describe the implementation of the program and its impact on improving student literacy. The study used a descriptive qualitative method with observation, interview, and documentation techniques. Data were analyzed through data condensation, data presentation, and conclusion drawing. The results showed that the habit of reading for 10 minutes helped improve students' reading fluency, increase vocabulary, train concentration, and foster interest in reading. The relevance to Islamic values further strengthens the meaning of this activity because students are accustomed to loving knowledge as part of Islamic teachings. Factors supporting success include teacher commitment, principal support, parental involvement, and the use of appropriate reading materials. Obstacles that emerged included limited reading materials and differences in student abilities.